«Әлеуметтік педагогика» пәнін оқытудың негіздері - Қабекенов, Ғ.У. (My University, 2013)
The problems of social pedagogics in the teaching process of High educational schools are analysed in this article . Also the books and textbooks on social pedagogics which were published in Kazakh language are discussed. The scientific- methodical analyse were done to the textbooks and books. The social pedagogics preferred the concretization of rules, contests and parts of the books and textbooks on social pedagogics in future.